Replication of enhancer-deficient amphotropic murine leukemia virus in human cells - Reuss, Frank U. (The National Academy of Sciences, 2001)
Amphotropic murine leukemia virus (MLV) replicates in cells from various mammalian species, including humans, and is a potential contaminant in MLV vector preparations for human gene transfer studies. The generation of replication-competent virus is considered less likely with vectors that delete the viral transcription elements. This conclusion is based on data obtained in rodents, where MLV replication depends on the expression of viral genes under the control of 75-bp enhancer elements in the long terminal repeat. We demonstrate here that in some human cells replication of amphotropic MLV is possible in the absence of these enhancer elements. Replication of the enhancer-deficient virus MLV-(MOA)ΔE is observed in selected human sarcoma and B lymphoma lines and proceeds at a lower rate than that of the intact virus. No insertion of a foreign promoter or enhancer into the long terminal repeat was detected. Our data suggest the presence of a secondary enhancer element within the MLV provirus that can in selected human cells mediate virus transcription and replication in the absence of the 75-bp U3 enhancers.